How Microsoft Windows Vista works - Miller, Michael, 1958- (Que, 2006)
Windows Vista is the long-awaited upgrade to Microsoft's Windows operating system, more than five years in the making. Millions of users are asking what's new about Vista, how does it differ from Windows XP, and how, exactly, does Windows Vista work? Those questions and more are answered in the new book, How Windows Vista Works, from best-selling author Michael Miller. How Windows Vista Works presents Vista from the inside out, with four-color graphics that illustrate the inner workings of the operating system. Readers will learn all about Vista's new features, including: - The Aero glass interface, Flip 3D, and other graphics features - The differences between Windows Vista Basic, Home Premium, Ultimate, and other versions - Internet Explorer 7, Windows Mail, and other Internet features - Windows Media Player 11, Windows Photo Gallery, and other digital media features - Windows Media Center, CableCARD and HDTV support, and other home entertainment features - Windows Explorer, Virtual Folders, and other new file management features - Windows Defender, User Account Control, and other new security features - SuperFetch, Fast Boot and Resume, and other new operating features Everything you need to know about how Windows Vista works and how it differs from previous versions of windows is illustrated in this book.